Acute Pulmonary Hemorrhage: Multidisciplinary Perspectives in Respiratory, Anesthesia, and Emergency Care - Humayyim, Khalid Abdullah Mohammed Bani; Qusai Jubarah Aljubarah; Yahia Ali Mashragi; Abdullah Ibrahim Almadhari; Yasser Emad Alharbi; Bader A. Alfawzan; Ameerah Abdullah Aleisawi; Hadi Ali Mobarki; Yazeed Abdullah Salem Alhumaidi; Homoud Mohammed Alsubaie; Ahmed Hulayyil Alruwaili; Abdullah Hussain Alyousef; et al. (Saudi Journal of Medicine and Public Health, 2024)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Pulmonary hemorrhage is a life-threatening condition characterized by bleeding from the lower respiratory tract, most often presenting as hemoptysis. Its severity ranges from minor, self-limited episodes to massive hemorrhage causing airway obstruction, respiratory failure, and hemodynamic collapse. The bronchial arterial circulation accounts for the majority of clinically significant cases, and etiologies vary globally, including tuberculosis, bronchiectasis, malignancy, and infectious or inflammatory lung diseases. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to provide a multidisciplinary overview of the etiology, epidemiology, pathophysiology, evaluation, and management of pulmonary hemorrhage, emphasizing contemporary evidence-based clinical practices. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The manuscript synthesizes findings from major cohort studies, prospective analyses, and current clinical guidelines. It integrates data on causes, regional variations, diagnostic strategies, interventional options, and outcomes to present a comprehensive overview for respiratory, anesthesia, and emergency care teams. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Evidence shows that massive hemoptysis comprises a small proportion of total cases but carries high mortality if not promptly managed. CT imaging provides superior diagnostic accuracy compared to chest radiography and often surpasses bronchoscopy for localization. Modern bronchial artery embolization achieves initial hemostasis in up to 90% of patients, though rebleeding occurs in approximately 30%. Airway stabilization, bronchoscopic interventions, anticoagulation reversal, and adjunctive therapies such as tranexamic acid are effective components of acute management. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Pulmonary hemorrhage requires rapid diagnosis, airway protection, multidisciplinary coordination, and timely interventional therapy. Advances in imaging, bronchoscopy, and embolization have significantly reduced mortality, but recurrence and complications remain substantial concerns.